Conservation Contour Trenching in Mizoram- A Case Study - Satapathy, K.K.; Bundela, D.S.; Goswami, S.N.; Pathak, K.A. (Journal of Soil and Water Conservation, 2022)
Shifting cultivation widely prevalent in Mizoram is eroding natural resource base drastically. Recently, a new contour trench farming system has heal initiated in Mizoram to transform shifting cultivation into settled cultivation based on scientific and economical management of land and water resources. The response of farmers has been quite positive towards new system for transforming the traditional practice. In this paper, some observations on hydrological response and economics of contour trenching works in the state have been dealt with.